Metanotal gland of the genus Eidmanacris (Grylloidea, Phalangopsidae): taxonomic importance - Prado,Rogilene Aparecida (2005)
The present study compares the metanotal gland through scanning electron microscopy in five species of Eidmanacris: E. corumbatai Garcia, 1998, E. alboannulata (Piza, 1960), E. dissimilis Desutter-Grandcolas, 1995, E. larvaeformis (Chopard, 1938) and Eidmanacris sp. The general external configuration of the gland was determined by the presence of two median projections with apical opening and a cluster of bristles just above these projections. Although there is a general pattern for this gland, each species has its own pattern, which can be defined mainly by the arrangement of the bristles and the position of the median projections. Our results suggest the taxonomical importance of these structures, which should be better analyzed when describing species of the genus Eidmanacris. In addition, while observing the reproductive behavior of these species, we concluded that the release of this gland secretion is important for the success of mating.